Impact of elevated carbon dioxide and planting density on the growth and physiological responses of Stevia rebaudiana bertoni - A, Abzar; Sakimin, Siti Zaharah; ZE Jaafar, Hawa; Tajidin, Nor Elliza; Berahim, Zulkarami; Ismail, Mohd Firdaus (Universiti Putra Malaysia, 2025)
Stevia rebaudiana Bertoni produces steviol glycosides (SGs) which are 300-400 times sweeter than table sugar, non-caloric in nature, and used by diabetic patients worldwide. Increasing level of carbon dioxide (CO2) in the atmosphere, due to environmental pollution and climate change, have the potential to influence crop growth and productivity including stevia. Additionally, planting density is another important agronomic factor that affects crop yield, but its interaction with CO2levels in stevia has not been adequately studied. Therefore, the current study was conducted with the objective to investigate the effects of elevated CO2(eCO2) under different planting densities on the growth and physiological responses of Stevia rebaudiana. A factorial (2×3) experimental design was employed, with two CO2levels (400 ppm as ambient CO2[aCO2] and 1200 ppm as eCO2) and three planting densities: high-density vertical (HDV), high-density horizontal (HDH), and low-density horizontal (LDH). Growth data were collected monthly until the final harvest, while physiological parameters were recorded at 1st and 3rd month after planting (MAP). The results indicated that eCO2significantly enhanced plant growth, with the highest plant height (77.1 cm) observed in eCO2-treated plants compared to aCO2(66.5 cm) at final harvest. Under aCO2HDH and HDV treatments resulted in taller plants than LDH at 1st MAP, but no significant differences were found at later stages. eCO2-treated plants also showed increased branching (25%–28% more at 1st–4th MAP) compared to aCO2-treated plants. Photosynthesis rates were 36% and 42% higher in eCO2plants at the 1st and 3rd MAP, respectively. LDH plants demonstrated better overall physiological performance, including higher photosynthetic rates and water use efficiency. In conclusion, eCO2significantly improves stevia growth and physiology, with LDH and HDH densities showing superior performance. These results suggest that optimizing both CO2levels and planting density can improve stevia productivity, particularly under future climate conditions